Obtaining Multicomponent Coatings of a Stable Composition for Electromagnetic Radiation Screens - V. A. Zelenin; E. O. Narushko; A. D. Gladinov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
The formation processes of coatings of Cu–Ni and Ag–Cu systems with a stable elemental composition by the method of electron-beam evaporation are considered. It is shown that in the zone of action of the electron beam on the ingot placed in the crucible at the total vapor pressure of the alloy elements Σp above the pressure under the cap of the installation, the melt boils, and in the outer zone adjacent to the melt zone, the process of sublimation of the hard alloy occurs. The microrelief and elemental composition of the surface layer of the Cu–Ni alloy ingot in the zones of evaporation and sublimation, as well as the elemental composition of the coatings deposited in this case, have been studied. It is shown that the most acceptable way to obtain coatings of the Cu–Ni system with a stable elemental composition is the simultaneous electron-beam evaporation of copper and nickel from two crucibles. The azeotropic composition of the alloy of the Ag–Cu system was calculated and experimentally verified. The research results are used in the manufacture of multilayered screens of electromagnetic radiation.